Pengaruh Pemeraman Terhadap Stabilisasi Tanah Laterit Campuran Zeolit Aktivasi Waterglas Terhadap Nilai California Bearing Ratio - David Bangguna (Potensi: Jurnal Sipil Politeknik, 2023)
Soil is the base of construction, both building construction and road construction. One of the poor soil conditions is determined by the amount of soil bearing capacity (CBR) value. The objective of this study is to obtain the effect of curing time on the CBR value of a zeolite-stabilized laterite soil activated by waterglass. This test is guided by ASTM for each test. The laterite soil dominated by iron oxidation in brownish red FeO. The stabilizing material zeolite contains crystalline minerals of alumina silicate SiO2 having four main functions, namely ion exchanger, adsorption filter, catalyst and molecular sieving. While waterglass dominated by sodium meta silicate. Stabilization conducted using 4%, 8%, 12%,16% natural zeolite compared to dry weight of the soil and waterglass equals to 6% of dry weight of laterite soil. Specimen tested on curing time of 0, 7 and 14. Test result shows the CBR result untrated soil 18,70% and increasing along with zeolite addition and along with increasing curing time. CBR value of laterite soil stabilization using zeolite activated by waterglass increased 2 to 3 times with the increasing CBR value of 38,82%, 41,81% and 46,46% at 14 days of curing time.